School Based Management in Improving Students' Skill Competence TKR Expertise Concentration SMKN 1 Bendo Magetan - Mahmudah, Indun; Nuryanto, Heru; Ihtifazhuddan, Razan; Joko, Joko; Basuki, Ismet (Civiliza Publishing, Indonesia., 2025)
School-based management (SBM) is an approach that gives autonomy and responsibility to schools in managing resources to improve the quality of education. This study aims to explore the implementation of MBS in improving student competencies in the Light Vehicle Engineering (TKR) expertise program at SMKN 1 Bendo Magetan. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. The purpose of this study is generally to determine the activities of the management process of teaching staff in improving professional competence at SMKN 1 Bendo Magetan. This research uses qualitative research and case study design. Data collection techniques used in this research are interviews, observation and documentation. The substantive findings of this research are (1) Curriculum Management and Competence of learning program management expertise of both teachers and students. (2) Student management to improve the competence of students majoring in TKR in forming students who are ready to work through additional activities and practical hours, students are given Islamic religious values such as reading walqiah, BTQ, praying in congregation so that the quality of education is truly as expected both for the students themselves and when they work in the midst of society. (3) Management of Facilities and Infrastructure. school facilities and infrastructure is one of the components in the school system. therefore its existence must be in harmony with other components. n increasing the competence of the expertise of the students, SMKN 1 Bendo Magetan provides additional hours for students and increases the practice of field work for students to be able to be competitive and can keep up with existing developments. Because in addition we cooperate with several MOU companies such as PT, CV the school also makes a Special Work Exchange (BKK) is an institution formed to support the expertise competence of students majoring in TKR